Prevalence and determinants of acute respiratory infections among under-five children in a tertiary care center at Pokhara, Nepal - Poudel, Pramila; Soti, Harikala (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Acute respiratory infection (ARI) is a major determinant of morbidity and mortality among under-five children in developing countries. Despite decreasing trends in childhood morbidity and mortality, ARI remains a significant predictor of recurrent illness and hospitalization among under-five children in Nepal. This study was conducted to assess the prevalence and determinants of ARI among under-five children at a tertiary care center at Pokhara, Nepal. Methods: An analytical cross-sectional study was conducted among 358 mother-child dyads who were recruited through a purposive sampling technique and data was collected through the computer-assisted personal interview (CAPI) technique. Descriptive and inferential statistics were used. The level of statistical significance was set at p<0.05. Results: The prevalence of ARI among under-five was 39.38%. The age of the child (AOR=8.37, 95% CI:5.00–13.99), being male (AOR=3.13,95% CI: 2.00–4.86), mother’s education below secondary level (AOR=2.28, 95% CI:1.39–3.73), child with no EBF (AOR=1.86, 95% CI:1.21–2.86), stunted child (AOR=2.99, 95% CI: 1.93–4.64), wasted child (AOR=2.66, 95% CI:1.71–4.12), passive smoking by child (AOR=2.43, 95% CI: 1.49–3.97), having no separate kitchen (AOR=0.18, 95% CI: 0.11–0.29) were found to be significant determinants of ARI. Conclusions: More than 1/3rd of the under-five children had ARI. Age and gender of the child, maternal education, breastfeeding and nutritional status of the child, passive smoking, not having a separate kitchen, and using wood as a cooling fuel were the determinants of ARI among under-five children. The occurrence can be minimized by improving households, the nutritional status of children, and by increasing awareness regarding its prevention and management.